New records of Uromyces erythronii (Pucciniales) from Ukraine - Tykhonenko, Yu.Ya.; Sytschak, N.N.; Kagalo, A.A.; Orlov, O.O. (Український ботанічний журнал, 2017)
Specimens of the rust fungus Uromyces erythronii were recorded on Erythronium dens-canis, a rare species listed in the
Red Data Book of Ukraine, in April 2016 near Chemeryntsi village (Lviv Region, Ukraine) and in May 2016 near Zaluzhne
village (Zhytomyr Region, Ukraine). An investigation of the Erythronium specimens deposited in the herbaria of vascular plants
of Lviv Natural History Museum (LWS) and M.G. Kholodny Institute of Botany (KW) revealed four more samples of this
fungus. A list of all localities in which U. erythronii was recorded in Ukraine is provided. The article is illustrated by micrographs
obtained by scanning electron microscopy. У квітні 2016 р. поблизу с. Чемеринці (Львівська обл.), а
у травні 2016 р. поблизу с. Залужне (Житомирська обл.)
були зібрані зразки гриба Uromyces erythronii на Erythronium dens-canis – рідкісній рослині, внесеній до Червоної
книги України. У результаті дослідження зразків Erythronium, які зберігаються у гербаріях судинних рослин
Львівського природознавчого музею (LWS) та Інституту ботаніки ім. М.Г. Холодного (KW), було виявлено ще
чотири випадки розвитку цього гриба. У статті наведено
список усіх локалітетів, в яких U. erythronii був зареєстрований в Україні. Робота ілюстрована мікрофотографіями, отриманими за допомогою сканувального електронного мікроскопа. В апреле 2016 г. в окрестностях с. Чемеринцы (Львовская обл.), а в мае 2016 г. в окрестностях с. Залужное
(Житомирская обл.) были собраны образцы гриба
Uromyces erythronii на Erythronium dens-canis – редком
растении, занесенном в Красную книгу Украины. В
результате исследования образцов Erythronium, хранящихся в гербариях сосудистых растений Львовского
природоведческого музея (LWS) и Института ботаники
им. Н.Г. Холодного (KW), было выявлено еще четыре
случая развития этого гриба. В статье приведен список
всех локалитетов, в которых U. erythronii был зарегистрирован в Украине. Работа иллюстрирована микрофотографиями, полученными с помощью сканирующего
электронного микроскопа.